Tinjauan Hukum Pidana Islam terhadap Pengaturan Justice Collaborator: Analisis Pasal 10A Ayat 3 UU Nomor 31 Tahun 2014 - Anindi Yuli Fauziah; Deden Najmudin; Yusup Azazy (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This research aims to analyze the legitimacy and position of the justice collaborator within the Indonesian criminal justice system and to assess its compatibility with the principles of Islamic criminal law. The method used in this research is a normative juridical approach with statutory and conceptual approaches. The research data were obtained through a literature study of primary legal materials in the form of legislation, the Supreme Court Circular Letter Number 4 of 2011, as well as Islamic legal sources such as the Qur’an, Hadith, and literature on fiqh jinayah. The results of the study indicate that the regulation of justice collaborators in Indonesian positive law provides legal protection and recognition in the form of sentence reductions for perpetrators who cooperate in revealing crimes. From the perspective of Islamic criminal law, this concept can, in principle, be accepted through the approach of tahfif al-‘uqubah (mitigation of punishment), taubat nasuha (sincere repentance), and considerations of public benefit (maslahah mursalah). This research finds a point of convergence between national law and Islamic law, particularly in efforts to realize substantive justice and the protection of public interests.